قراءة إيبيستيمولوجية لظاهرة التهرب الضريبي في الحقل السوسيولوجي - صاولي, هشام; زعاف, خالد (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة الى البحث في إمكانية معالجة ظاهرة التهرب الضريبي، معالجة سوسيولوجية بعيدا عن المنحى التبريري الذي تتسم به الدراسات الاقتصادية والقانونية في معالجتها لهذه الظاهرة، محاولين في ذلك مقاربة الظاهرة وفق نظريات تنتمي إلى الحقل المعرفي السوسيولوجي بدءًا بالمقاربة الخلدونية، ثم المقاربة الوظيفية و النقدية وانتهاء بنظرية التشكيل لأنتوني غيدنز. و قد خلص هذا العمل إلى أهمّ مجالات الفعل الضريبي التي يمكن للسوسيولوجيا أن تخوض فيها دراسة وبحثا وفق أدواتها المنهجية و النظرية التي تميزها عن الحقول المعرفية الأخرى، ما يمكننا من فهم وتفسير ظاهرة التهرب الضريبي والكشف عن الأنساق الخفيّة التي تتحكم فيها . This study aims to investigate the possibility of treating the phenomenon of tax evasion, a sociological treatment far away from the justification approach that characterizes economic and legal studies in their treatment of this phenomenon, and we try to approach the phenomenon according to theories that belong to the sociological field starting with the Khaldunic approach, then the functional and critical approach and ending with the formation theory by Anthony Giddens. This work concluded to the most important areas of tax action, in which sociology can study and research according to its methodological and theoretical tools that distinguish it from other fields of knowledge, which enables us to understand and explain the phenomenon of tax evasion and uncover the hidden systems that control it.
مقال
Keywords: الضريبة ; التهرب الضريبي ; الحقل السوسيولوجي